(untitled) (International Journal of Language, Literacy and Translation, 2025)
The ability to speak English proficiently has become increasingly important in the job market, especially in a diverse country like Malaysia. This brief aims to explore the significance of speaking English during job interviews in Malaysia, focusing on its impact on employability and career opportunities. The objective of this study is to examine how speaking English during job interviews affects employability in Malaysia. It attempts to identify company expectations and ascertain how well-rounded English language abilities affect employment possibilities. A mixed-methods strategy will be used to achieve this goal. A literature study will be done first to acquire information from previously conducted research on the topic. Furthermore, a series of online surveys will be conducted with Malaysian companies to get their perspectives on the significance of English language skills in the context of job interviews. The data collected will be analysed to identify common themes and patterns. The findings of this research are expected to highlight the importance of English-speaking skills in Malaysian job interviews. Employers are expected to place significant value on candidates who can communicate fluently in English, as it is seen as a crucial skill for effective collaboration, customer service, and international business interactions. The study may also reveal specific industries or job roles where English proficiency is particularly desirable. In conclusion, the ability to speak English proficiently during job interviews positively impacts employability in Malaysia. Employers often prioritise candidates who can communicate effectively in English, enhancing their chances of success in diverse work environments and global business interactions. By recognising the importance of English-speaking skills and investing in language proficiency, job seekers can enhance their employability and open doors to a wider range of career opportunities in Malaysia.